2003
DOI: 10.1074/jbc.m211093200
|View full text |Cite
|
Sign up to set email alerts
|

P-glycoprotein (MDR1) Expression in Leukemic Cells Is Regulated at Two Distinct Steps, mRNA Stabilization and Translational Initiation

Abstract: Multidrug resistance in acute myeloid leukemia is often conferred by overexpression of P-glycoprotein, encoded by the MDR1 gene. We have characterized the key regulatory steps in the development of multidrug resistance in K562 myelogenous leukemic cells. Unexpectedly, up-regulation of MDR1 levels was not due to transcriptional activation but was achieved at two distinct posttranscriptional steps, mRNA turnover and translational regulation. The short-lived (half-life 1 h) MDR1 mRNA of naïve cells (not exposed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
132
0
8

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(156 citation statements)
references
References 55 publications
12
132
0
8
Order By: Relevance
“…Simultaneous treatments with the transcription inhibitor ActD suggested that these up-and downregulations occurred at the transcriptional level without any change in mRNA stability as reported in leukaemic cells (Yague et al, 2003). De novo protein synthesis inhibition with CHX did not suppress TSA-mediated ABCB1 modulations, suggesting that TSA influence mainly this gene transcription directly at the chromatin level.…”
Section: Discussionmentioning
confidence: 55%
“…Simultaneous treatments with the transcription inhibitor ActD suggested that these up-and downregulations occurred at the transcriptional level without any change in mRNA stability as reported in leukaemic cells (Yague et al, 2003). De novo protein synthesis inhibition with CHX did not suppress TSA-mediated ABCB1 modulations, suggesting that TSA influence mainly this gene transcription directly at the chromatin level.…”
Section: Discussionmentioning
confidence: 55%
“…Despite overexpression of ABCB1 mRNA, two independent studies identified a block in the translation of ABCB1 mRNA within K562 cells. 18,19 Although the possibility exists within our MCF-7 cell lines that all transcripts produced are not translated into protein, the high Abcb1 protein expression levels within MCF-7 EPI and MCF-7 TAX-2 indicates that a translational blockade was not present in these drug-resistant cell lines. Gene amplification is also a potential mechanism for increased ABCB1 transcription, given previously published findings using a variety of drug-resistant cancer cell lines.…”
Section: Discussionmentioning
confidence: 97%
“…A region with strong hypomethylation induced by selection for drug resistance spans CpG sites 49-66. Shared valleys of hypomethylation in drug-resistant and Azatreated cells span CpG sites [19][20][21][22], which correspond to the consensus Inr site, a site adjacent to the transcription start site (Table 3), and CpG sites 32-44 implicated in the regulation of ABCB1 expression by p53 (Table 4). Aza treatment did not result in dramatic reduction in the methylation of CpG sites 49-66 (Figure 5f).…”
Section: Discussionmentioning
confidence: 99%
“…Amplification and detection were carried out by using an ABI PRISM 7700 detection system (Applied Biosystems) as fol- Results were normalized to the housekeeping gene β-actin for the study of transcriptional activity and mRNA half-life. To compare the expression levels among different samples, the relative expression of mRNA levels was calculated using the comparative delta C T (threshold cycle number) method as described previously [29]. Briefly, the following formula was used: 2 -DDC T , where DC T is the difference in C T between the gene of interest and β-actin, and DDC T for the sample=DC T for the actual sample-DC T of the lowest expression sample.…”
Section: Determination Of Mrna Levels By Quantitative Real-time Pcrmentioning
confidence: 99%